2008
DOI: 10.3171/jns/2008/108/4/0689
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular decompression for trigeminal neuralgia in elderly patients

Abstract: Microvascular decompression is an effective treatment for elderly patients with TN. The authors' experience suggests that the rate of complications and death after MVD for TN in elderly patients is no different from the rate in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…There was also no difference in terms of length of hospital stay between the two groups. These results agree with the few reports that appear in the literature 14,18) . The most frequently reported complications of MVD include hearing loss, diplopia, facial palsy, brainstem or cerebellar infarct, hematoma, ataxia, CSF leak, meningitis, and hydrocephalus 4,15) .…”
Section: Discussionsupporting
confidence: 83%
“…There was also no difference in terms of length of hospital stay between the two groups. These results agree with the few reports that appear in the literature 14,18) . The most frequently reported complications of MVD include hearing loss, diplopia, facial palsy, brainstem or cerebellar infarct, hematoma, ataxia, CSF leak, meningitis, and hydrocephalus 4,15) .…”
Section: Discussionsupporting
confidence: 83%
“…Because of its high rate of success, MVD is considered by many to be the optimal initial treatment for typical TN in young and elderly otherwise healthy adults. 1,17 In considering MVD for TN, the utility of distinguishing between the various subtypes of TN is becoming clearer. In reviewing Jannetta's 7 results over a 24-year period, Tyler-Kabara et al 23 have shown that patients with typical TN fare far better than those with atypical TN.…”
Section: Discussionmentioning
confidence: 99%
“…3,22,32 As the world's population ages, the safety of MVD in older persons has become a topic of increased interest. 2,8,9,12,13,25,27,29,30 To date, the safety of MVD in older patients has been examined through several small case series, which were * CHF = congestive heart failure. …”
Section: Discussionmentioning
confidence: 99%
“…The age cutoffs range from 60 years in 1 study, 2 65 years in 4 studies, 8,9,25 70 years in 1 study, 12 to 75 years in 2 studies. 27,30 Cumulatively, these studies examine 441 older patients, with attention to multiple complications including death, stroke, cerebellar hematoma, cranial nerve injury, CSF leak, and infection. Authors of these studies independently report that older patients do not have an increased risk of death, stroke, cerebellar hematoma, or cranial neuropathy, and this conclusion remains when analyzed collectively through a meta-analysis.…”
Section: Fig 3 Bar Graphs Demonstrating the Average Hospital Los (Lmentioning
confidence: 99%
See 1 more Smart Citation